The Effect of CSR Disclosure on Financial Performance Companies Listed on the Indonesia Kompas-100 Index 2018-2020 - Muhammad Erwin ALTHAF; Zuliani DALIMUNTHE; Imbuh SULISTYARINI; Hendro PRABOWO (Communications of International Proceedings, 2021)
This study aims to examine the effect of CSR disclosure on company performance among Indonesian companies listed on the Kompas 100 Index during 2018-2020. The company's performance uses four different measures: sales, net profit margin (NPM), return on assets (ROA), and Tobin's Q. This study uses secondary data. The data comes from sustainability reports published by each company based on the Global Reporting Initiative (GRI) standards, and financial data comes from the Osiris database. This study uses regression analysis by processing cross-sectional data. This study indicates that CSR disclosure in the previous year has a significant positive effect on sales but has a negative effect on net profit margin. However, this study finds no evidence that CSR disclosure affects performance as measured by ROA and Tobin's Q.  This finding indicates that although CSR disclosure has a positive impact on sales, it creates higher cost increases so that it does not impact the company's overall performance as measured by ROA. Meanwhile, the regression results to Tobin's Q show that investors do not significantly respond to CSR disclosure. These findings indicate that disclosure of a firm's CSR activities is perceived as more in compliance with the rules than the company's commitment to maintaining sustainability according to the three-bottom-line concept.
Keywords: Corporate Social Responsibility; Tobin’s Q; Financial Performance; Three-bottom-line Concept.